Pathway of effects of adverse childhood experiences on psychological distress and substance use among emerging adults: A structural equation modeling approach - Ajith K. Remesan; Varalakshmi Chandra Sekaran; Satyanarayana Poojari; Teddy Andrews Jaihind Jothikaran; Vani Lakshmi R; Lena Ashok (Clinical Epidemiology and Global Health)
Background: Adverse childhood experiences (ACEs) refer to various types of abuse, neglect, and household dysfunction that individuals may experience in childhood. These experiences can lead to significant long-term effects on mental health and behavior. Individuals with higher ACE scores are more likely to experience psychological distress and the uptake of substances. This study aimed to explore the relationship between ACEs, psychological distress, and substance use among emerging adults. Methods: The cross-sectional study was conducted in the Udupi district of Karnataka, India. The undergraduate colleges associated with Mangalore University were the sampling units. A multi-stage cluster random sampling method was employed to select 12 colleges from the undergraduate institutions in the district affiliated with Mangalore University based on their various courses. Data was collected in a classroom setting among 957 emerging adults between June 2023 and October 2023. Results: Among the participants, 18.91 % reported ACEs. Additionally, the prevalence of psychological distress and substance use were noted to be 27.03 % and 17.97 %, respectively. Tobacco and alcohol were having a higher prevalence in comparison with other substances. Furthermore, emerging adults who have experienced ACEs are significantly more prone to experiencing psychological distress. Conclusion: The study highlights the connection between ACEs, psychological distress, and substance use in emerging adults. It calls for integrating ACEs into interventions and policies, emphasizing the need for global research, particularly in India, to foster social cohesion and well-being through prevention and early detection strategies.